PRELIMINARY ECONOMIC ANALYSIS OF SPINY LOBSTER, Panulirus homurus CULTURE IN FLOATING NET CAGE IN EKAS BAY EAST LOMBOK - Anak Agung Alit; Titiek Aslianti; Bejo Slamet (Indonesian Aquaculture Journal, 2006)
Spiny lobster, Panulirus homurus